2018
DOI: 10.3390/rs10091373
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of the Successive GPM Based Satellite Precipitation Estimates IMERG–V03, –V04, –V05 and GSMaP–V06, –V07 Over Diverse Geomorphic and Meteorological Regions of Pakistan

Abstract: Launched in 2014, the Global Precipitation Measurement (GPM) mission aimed at ensuring the continuity with the Tropical Rainfall Measuring Mission (TRMM) launched in 1997 that has provided unprecedented accuracy in Satellite Precipitation Estimates (SPEs) on the near-global scale. Since then, various SPE versions have been successively made available from the GPM mission. The present study assesses the potential benefits of the successive GPM based SPEs product versions that include the Integrated Multi-Satell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 45 publications
2
32
0
Order By: Relevance
“…Zhao et al (2018) and Wei et al (2018b) showed that V03 outperforms V04 over China. Satgé et al (2018), who compared IPPs V03, V04, and V05 over Pakistan, indicated V04 works worse than V03. However, V05, with a real enhancement, estimates precipitation with more accuracy in comparison with V03 and V04.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhao et al (2018) and Wei et al (2018b) showed that V03 outperforms V04 over China. Satgé et al (2018), who compared IPPs V03, V04, and V05 over Pakistan, indicated V04 works worse than V03. However, V05, with a real enhancement, estimates precipitation with more accuracy in comparison with V03 and V04.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the high resolution of IPPs and significant uncertainties arising from interpolation of the daily data of 76 synoptic stations across Iran (due to the lowdensity of stations), we applied a point-to-pixel approach for evaluations in this study like many previous studies, for example, Xu et al (2017), Rivera et al (2018), Wei et al (2018a), and Satgé et al (2018). To assess the validity of IMERG products over Iran, we considered continuous validation metrics such as modified Kling-Gupta efficiency (KGE), relative bias (RBias), correlation coefficient (CC), and root-mean-square error (RMSE); as well as categorical validation metrics such as probability of detection (POD), false alarm ratio (FAR), critical success index (CSI), and Heidke skill score (HSS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gauge-calibrated product of standard GSMaP_MVK is GSMaP_Gauge, which adjusted by daily CPC gauge data. Many studies have assessed and compared the performances of GSMaP_Gauge over the last few years and have shown that GSMaP_Gauge is a satisfactory gauge-adjusted satellite precipitation estimation around the world, especially over East Asia [34][35][36][37][38].Recently, in the GSMaP project, the GSMaP_Gauge_NRT was produced by a GSMaP algorithm team, aiming to improve the accuracy of near-real-time product of GSMaP (i.e., GSMaP_NRT) and maintain its timeliness. Section 2.2 describes the calibration procedure of GSMaP_Gauge_NRT in detail.…”
mentioning
confidence: 99%
“…Satgé et al [25] present an assessment of the potential benefits of the successive GPM-based SPEs product versions that include the Integrated Multi-Satellite Retrievals for GPM (IMERG) version 3 to 5 (-v03, -v04, -v05) and the Global Satellite Mapping of Precipitation (GSMaP) version 6 to 7 (-v06, -v07). The analysis is conducted over different geomorphic and meteorological regions of Pakistan while using 88 precipitation gauges as a reference.…”
Section: Overview Of Contributionsmentioning
confidence: 99%